Synthesis and Characterization of SnO2 and SnO2/ZnO Nanoparticles by Electrochemical Method: Evaluation of their Performance in Photodegradation of Indigo Carmine Dye and Antibacterial Activity - Samskruthi, K.P.; Ananda, Sannaiah; Nandaprakash, M.B.; Chandrakantha, K.S. (Asian Journal of Chemistry, 2020)
SnO2 and SnO2/ZnO nanoparticles were synthesized by the electrochemical method. The synthesized nanoparticles were characterized by XRD, UV-VIS, IR, FE-SEM and EDAX techniques. The X-ray diffraction revealed that the average crystalline size to be 79.78 and 22.84 nm. The band gap of SnO2/ZnO nanoparticle from Tauc′s plot was found to be 2.196 eV. The photocatalytic degradation of Indigo carmine dye follows the first order reaction. The antibacterial activity of SnO2 and SnO2/ZnO nanoparticles against Staphylococcus aureus and Escherichia coli was investigated.